Curtobacterium allii sp. nov., the actinobacterial pathogen causing onion bulb rot - Manzeal Khanal; Bed Prakash Bhatta; Sujan Timilsina; Sudeep Ghimire; Kimberly Cochran; Subas Malla (Antonie van Leeuwenhoek, 2023)

Need for speed: bacterial effector XopJ2 is associated with increased dispersal velocity of Xanthomonas perforans - Anuj Sharma; Sujan Timilsina; Peter Abrahamian; Gerald V. Minsavage; James Colee; Peter S. Ojiambo; Erica M. Goss; Gary E. Vallad; Jeffrey B. Jones (Environmental Microbiology, 2021)
Summary Bacterial spot caused by Xanthomonas perforans ( Xp ) is an economically important disease in tomato. Previous studies have shown that the recently isolated Xp strains have acquired and retained the effector gene, xopJ2 , which has been reported to increase fitness of the pathogen in the field. To elucidate the fitness benefit of xopJ2 , we quantified the effect of xopJ2 on the dispersal and evolution of Xp populations on tomato. We compared movement of two wild‐type Xp strains expressing xopJ2 to their respective xopJ2 mutants when co‐inoculated in the field. We developed a binary logistic model to predict the presence of Xp over spatial and temporal dimensions with or without xopJ2 . Based on the model, wild‐type bacteria were dispersed approximately three times faster than the xopJ2 mutants. In a simulation experiment, the selective advantage due to increased dispersal velocity led to an increase in the frequency of xopJ2 gene in the Xp population and its apparent fixation within 10 to 12 cropping seasons of the tomato crop. Our results show that the presence of a single gene can affect the dispersal of a bacterial pathogen and significantly alter its population dynamics.

First occurrence of Diaphorina citri in East Africa, characterization of the Ca. Liberibacter species causing huanglongbing (HLB) in Tanzania, and potential further spread of D. citri and HLB in Africa and Europe - Mpoki M. Shimwela; Hossein A. Narouei-Khandan; Susan E. Halbert; Manjunath L. Keremane; Gerald V. Minsavage; Sujan Timilsina; Deogracious Protas Massawe; Jeffrey B. Jones; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2016)

Molecular characterization of Xanthomonas strains responsible for bacterial spot of tomato in Ethiopia - Misrak Kebede; Sujan Timilsina; Amare Ayalew; Belayneh Admassu; Neha Potnis; Gerald V. Minsavage; Erica M. Goss; Jason C. Hong; Amanda Strayer; Mathews Paret; Jeffrey B. Jones; Gary E. Vallad (European Journal of Plant Pathology, 2014)